2019
DOI: 10.3389/fpubh.2019.00369
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Care Service Utilization Among Adolescent Pregnant Women–Evidence From Swabhimaan Programme in India

Abstract: Purpose: Pregnant adolescent girls (15-19 years) are more vulnerable to poor health and nutrition than adult pregnant women because of marginalization and lack of knowledge about the antenatal care (ANC) services. The present study aims to test this hypothesis and assess determinants of ANC service utilization among currently adolescent pregnant women.Methods: Data were drawn from the baseline survey of SWABHIMAAN project, which had been conducted in three states of India: Bihar, Chhattisgarh, and Odisha. Out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 36 publications
6
24
0
1
Order By: Relevance
“…This finding is similar to a study conducted in Jimma University Specialized Hospital where 77% of respondents were satisfied [28]. This finding is not consistent with a study conducted in Belgium, at the University Hospital of Ghent (Belgium), Australia, Sweden, Nigeria, Shire North West Tigray, Bahir Dar, and Jimma town mothers in which majority of the study participants were satisfied by antenatal care services [13][14][15][16][17][18][19][20]. The difference might be due to competency, attitude, and skills of maternal care providers and overall service delivery structure differences between Ethiopia and European countries.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…This finding is similar to a study conducted in Jimma University Specialized Hospital where 77% of respondents were satisfied [28]. This finding is not consistent with a study conducted in Belgium, at the University Hospital of Ghent (Belgium), Australia, Sweden, Nigeria, Shire North West Tigray, Bahir Dar, and Jimma town mothers in which majority of the study participants were satisfied by antenatal care services [13][14][15][16][17][18][19][20]. The difference might be due to competency, attitude, and skills of maternal care providers and overall service delivery structure differences between Ethiopia and European countries.…”
Section: Discussionsupporting
confidence: 57%
“…Patients' use of health care is affected by the quality of care; those who are not satisfied with their providers may be less likely to continue with treatment or seek further services. According to the U.S. Agency for Healthcare Research and Quality, National Consumer Assessment of Healthcare Providers and Systems (CAHPS) Benchmarking Database in Africa, a maternal satisfaction survey was conducted at different times in different counties (for instance, in 2012 and 2018 and in Egypt and Nigeria, the level of maternal satisfaction with ANC was greater than 90% and 90%, respectively, whereas in Ethiopia, the levels of maternal satisfaction with antenatal care in 2008, 2013, 2014, 2018, and 2019 were 35%, 47.7%, 60.4%, 90%, and 90.8%, respectively [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…However, the highest rate of maternal complications (53, 44.16%) was identified among subjects with Pre-University Course/Diploma education. In addition, employed pregnant women tend to seek ANC during pregnancy, due to financial independence [18]. Only 8.84% study subjects were found to be employed (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Being single and at school, the teenager may hide the pregnancy and therefore not utilize the available antenatal care services. 5 She may also try to terminate the pregnancy late in gestation for the same reason and end up with life threatening compilations like uterine perforation, sepsis and even death. Pelvis is underdeveloped because of the young age.…”
Section: Introductionmentioning
confidence: 99%